Role of parents and friends in adolescents’ identity formation in Indonesia. - Muttaqin, Darmawan; Chanafi, Alfi Rossi; Nofelia, Baiq Irma Anggi; Khristi, Theodora Carelina; Wahyuningsih, Sri (Indigenous, 2022)
Abstract. The identity formation of adolescents in a collective society is dependent on their significant relationship with other people. Therefore, this study aims to examine the role of parents and friends in adolescents’ identity formation in Indonesia. This research was conducted using a quantitative survey method involving 489 adolescents with 142, 178, and 169 in their early, middle, and late adolescent phases ranging from 12 to 21 years. Data collection was carried out on adolescents who are currently studying in Surabaya by using the convenience sampling method. The Indonesian version of the UtrechtManagement of Identity Commitments Scale, Shortened Version of Child's Report on Parent Behavior Inventory, Friendship Quality Scale, and Caregiving Questionnaire were used to measure the dimensions of identity, parenting, friendship quality, and support-giving. The hierarchical regression analysis was used to determine the role of the dimensions of parenting, friendship quality, and support giving gradually to identity formation. The results showed that parenting, friendship quality, and support contribute to commitment (R2= 0.291), in-depth exploration (R2= 0.241), and reconsideration of commitment (R2 = 0.110). It also indicates that the adolescent's identity formation in Indonesia embraces a collective culture inseparable from authority figures and peer groups. The implication of this research is that differences in the quality and form of relationships with parents and friends can lead to differences in adolescent identity formation.Keywords: adolescents; friendship; identity formation; Indonesia; parenting.